Efficacy of School-based SEL Programs: Aligning with Health and Physical Education Standards. Issue 5 (12th June 2020) - Goh, Tan Leng; Connolly, Mary
Abstract : The Competencies and sub-competencies of the Collaborative of Academic and Social Emotional Learning (CASEL) are very closely aligned to skills-based health education based on the National Health Education Standards and SHAPE America Grade Level Outcomes but miles apart when it comes to recognizability, perceived need, efficaciousness, and implementation. It is the intent of this article to demonstrate how current research, which indicates the benefits of teaching and learning SEL skills, is related to the skills taught in health and physical education.